Projek Penguatan Profil Pelajar Pancasila dalam Pengembangan Kurikulum Merdeka di SD Negeri 2 Sukadana - Ahmad, Hariadi; Gunawan, I Made Sonny; Hartati, Aluh; Astuti, Farida Herna (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2024)
The implementation of community service carried out independently aims to provide an understanding of the Pancasila student profile guide project in the development of an independent curriculum in educational units, in the implementation of assistance carried out by the accompanying team, namely the Pancasila student profile acts as the main reference that directs educational policies including become a reference for educators in building the character and competence of students. Comprehensive assistance can improve educational units' ability to formulate policies more responsive to local needs and context. The Pancasila student profile consists of six dimensions, namely: 1) having faith, being devoted to God Almighty, and having noble character; 2) independent; 3) working together; 4) global diversity; 5) critical reasoning; and 6) creative. The six dimensions of the Pancasila student profile need to be seen as a whole unit so that each individual can become a competent lifelong learner who has character and behaves according to the values ​​of Pancasila. Educators need to develop these six dimensions comprehensively from early childhood education. In addition, to help a more comprehensive understanding of the dimensions of the Pancasila student profile, the meaning of each dimension is explained and its development is sequenced according to the psychological and cognitive development stages of school-aged children and adolescents.